Seeking Solution To Software Piracy In Teacher Education In An Age Of Ict - S. E., Nwana; S. O., Ugwuda (Advances in Social Sciences Research Journal, 2017)
The paper focuses on software piracy in teacher education. In this age of Information and Communications Technology (ICT) various software are used for teaching – learning effectiveness and many of them an reproduced by software pirates. In this paper, the concepts of teacher education, ICT and computer software were explained. Types of computer software were listed and explained. It highlighted software production and originality of works, under section 51 of the Copyright Act Cap. C 28 Laws of the Federation 2004. It defined piracy. It examined copyright and enumerated the things that constitute infringement of copyright as provided in section 15 (1) (a-g) copyright Act Cap. C 28 Laws of the Federation 2004. Finally, the paper stated legal remedies for curbing software privacy in teacher education. Also, it stated various way forward such as provision of storage facilities, software library and software encryption.